2019
DOI: 10.1017/ipm.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

The association between family dysfunction and admission to an acute mental health inpatient unit: a prospective study

Abstract: Objectives:With the shift from deinstitutionalization to community care in mental health services, relatives of persons with severe and enduring mental illnesses have had to take over the role as primary caregivers. Disturbed family dynamics have been observed within families with an ‘ill’ member. Although schizophrenia and related mental illnesses are biologically based disorders, environmental stress (including stress within family relationships) plays a major role in the onset and maintenance of symptoms. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…It appeared that patients with OCD who were single, who had more severe comorbid depressive symptoms, who used psychotropic medication, and who had a low quality of life were significantly more likely to have intensive treatment 2 years later. Our results on being single and more severe comorbid depression resemble the results concerning other mental disorders (18,19,21). Thus, also in patients with OCD, these variables predict future intensive treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It appeared that patients with OCD who were single, who had more severe comorbid depressive symptoms, who used psychotropic medication, and who had a low quality of life were significantly more likely to have intensive treatment 2 years later. Our results on being single and more severe comorbid depression resemble the results concerning other mental disorders (18,19,21). Thus, also in patients with OCD, these variables predict future intensive treatment.…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review of 58 papers on predictors of readmission in patients with several mental disorders indicates that previous hospitalization, younger age, being unmarried, having lower financial means, not being satisfied with the index treatment, having more hospital days on the index admission, and a negative attitude toward medication were predicting factors for psychiatric readmission (18). In addition, being male, having psychotic symptoms, a longer duration of untreated psychosis, less social satisfaction, disturbed family dynamics, residing in an urban area, and illegal drugs misuse were found predictive of hospitalization in recent prospective cohort studies involving several mental disorders (18)(19)(20)(21)(22). A population study combined several survey and register databases of 2,638 individuals born in 1953, including interviews with their mothers.…”
Section: Introductionmentioning
confidence: 98%
“…For this reason, the family ambit is assumed to be a vital determinant of human behaviour [ 3 , 4 ]. Family functioning directly influences the transmission of positive habits, in addition to impacting upon the way in which primary school students are raised by their parents [ 5 , 6 ]. It can lead to negative parental behaviours, which will impair later positive development of skills in members making up the family nucleus [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that parents of a child with mental health challenges felt that others were dismissive, misunderstood their child's disorder and viewed their child negatively [37]. Further, having a family member with a mental health disorder may act as a risk factor for poor family functioning [38]. This weakened family unit could, in turn, negatively affect the youth's wellbeing and heighten the possibility for maladaptive outcomes such as hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…This weakened family unit could, in turn, negatively affect the youth's wellbeing and heighten the possibility for maladaptive outcomes such as hospitalization. However, there is a need for greater research in this area as few studies have investigated the association between family dysfunction and mental health admissions specifically [38].…”
Section: Introductionmentioning
confidence: 99%